Perception of health trainees and workers from Long-Term Care Institutions for the Elderly on institutionalization - Pascotini, Fernanda dos Santos; Fedosse, Elenir (ABCS Health Sciences, 2018)
Introduction: With the increasing aging of the population, institutionalization expands, especially since, for the most part, it is the only option of housing and care for the elderly and/or their families. The conceptions of the professionals that work in institutions have repercussions on their behaviors and ways of attending/caring for health. Objective: To identify the perception of health trainees and workers from geriatric long-term care facilities (ILPI) about institutionalization. Methods: Qualitative and quantitative study through a questionnaire filled out by ILPI trainees and workers. Data interpreted from descriptive data analysis and content analysis. Results: 40 individuals participated in the research, 65% of which were health trainees and 35% were workers. As for the positive aspects of institutionalization, two categories emerged: emotional assistance (support and security, caring and socialization among the elderly) and physical assistance (specialized care and accessibility). As for the negative aspects, three categories emerged: estrangement from the outside world (detachment from the family, material goods and social isolation), imposed rules (routine of the institution, lack of privacy/freedom and absence of leisure) and professional care (lack of specialties and unprepared professionals). When asked whether they would live in a ILPI in old age, 22 answered yes. Conclusion: There is a need to follow up the study, suggesting strategies capable of minimizing the negative aspects of institutionalization in this ILPI, detected by the sample, and maximizing/improving the positive aspects. It is the role of workers to continually improve themselves to improve the working conditions of the institutions in which they work.